Evaluating the success rate of 155 dental implants 2 years post delivery - AR. Rokn; M. Paknezhad (Tehran University of Medical Sciences, 1996)
In a 2 year study, indices of implant health such as PPD, PAL, BI and GI were measured and compared at the baseline, 6 months, 1 and 2 years after implant delivery.  It  was found that PPD and PAL indices were decreased in second year in compare to the first year which implicates success and health of implant in a 2 year period following prosthesis insertion.